THE HITCHHIKER’S GUIDE TO COMMUNITY: TERRITORIALITY, INTIMACY AND OWNERSHIP IN ONLINE SPACES - Rambukkana, Nathan (AoIR Selected Papers of Internet Research, 2015)
This paper demonstrates how the ownership of online communities, the interactions between community users and the owners/managers of those communities, and the internal politics that can arise between types of users can, together, alter the complexion of the spaces those communities create, as well as the intimacies (Berlant, 2000) those spaces afford as social technologies (Baym, 2010). In addition, working the language of social network analysis together with older work on politics of “the virtual community” enables a rethinking of online community politics over longer timespans and with more nuanced problematics and articulations than were available for consideration during that earlier period of study. This paper employs a longitudinal virtual ethnography (Hine, 2000; Silver, 2003) of the website and community surrounding The Hitchhiker’s Guide to the Galaxy Online (h2g2.com), with three periods of engagement in 1999, 2004 and 2014 (years 1, 5 and 15 of the Guide). The paper uses discourse analysis in conjunction with grounded and participant observation, informal interviews and semi-structured themed discussion threads on site to unpack the issues that arose during each period and in conjunction with the website having three separate owners: company that originally created the site, the BBC, and most recently a new company run by one of the site’s original owners.